Neuropsychology of memory - Squire, Larry R.; Butters, Nelson (Guilford, 1992)
Section I. Studies of normal and abnormal memory in humans * A neuropsychological model of memory and consciousness / Morris Moscovitch * What are the functional deficits that underlie amnesia? / Andrew R. Mayes * The role of fluency in the implicit and explicit task performance of amnesic patients / Laird S. Cermak and Mieke Verfaellie * Awareness, automaticity, and memory dissociations / Jeffrey P. Toth, D. Stephen Lindsay, and Larry L. Jacoby * Memory dissociations: A cognitive psychophysiology perspective / Russell M. Bauer and Mieke Verfaellie * Selective knowledge loss in activational and representational amnesias / Elkhonon Goldberg and William B. Barr * The contributions of emotional and motivational abnormalities to cognitive deficits in alcoholism and aging / Marlene Oscar-Berman * The problem of "localizing" memory in focal cerebrovascular lesions / D. Yves von Cramon and Hans J. Markowitsch * Learning and memory in humans, with an emphasis on the role of the hippocampus / Raymond P. Kesner, Ramona O. Hopkins and Andrea A. Chiba * Functional significance of etiological factors in human amnesia / Alan J. Parkin * The "new" and the "old": Components of the anterograde and retrograde memory loss in Korsakoff and Alzheimer patients / Michael D. Kopelman * Transient global amnesia / Mark Kritchevsky * Detecting amnesia's impostors / Jason Brandt * Systems of motor skill / Daniel B. Willingham * Impaired priming in Alzheimer's disease: Neuropsychological implications / David P. Salmon and William C. Heindel * The mobilization of procedural learning: The "key signature" of the basal ganglia / J. A. Saint-Cyr and A. E. Taylor * Procedural and declarative learning: Distinctions and interactions / Mary Jo Nissen * The assessment of memory disorders in patients with Alzheimer's disease / Marilyn S. Albert and Mark B. Moss * Degraded knowledge representations in patients with Alzheimer's disease: Implications for models of semantic and repetition priming / Alex Martin * Semantic memory dysfunction in Alzheimer's disease: Disruption of semantic knowledge or information-processing limitation? / Robert D. Nebes * A transfer-appropriate processing account for memory and amnesia / Peter Graf and Karen A. Gallie * Age-related changes in explicit and implicit memory / Hasker P. Davis and Patricia A. Bernstein * Aging and memory: A model systems approach / Paul R. Solomon and William W. Pendlebury * Cholinomimetic therapy in Alzheimer's disease / Leon J. Thal * A strategy for studying memory disorders in multiple sclerosis / William W. Beatty * Posttraumatic and retrograde amnesia after closed head injury / Harvey S. Levin, Matthew A. Lilly, Andrew Papanicolaou and Howard M. Eisenberg * Implicit memory and errorless learning: A link between cognitive theory and neuropsychological rehabilitation? / Alan D. Baddeley * Rehabilitation and memory disorders / Barbara A. Wilson Section II. Studies of monkeys and rodents * The components of the medial temporal lobe memory system / Stuart Zola-Morgan and Larry R. Squire * The role of the hippocampus-fornix-mammillary system in episodic memory / David Gaffan * A hypothesis on primal long-term memory: Neurophysiological evidence in the primate temporal cortex / Yasushi Miyashita, Han Soo Chang and Koichi Mori * Aging, memory, and cholinergic systems: Studies using delayed-matching and delayed-nonmatching tasks in rats / Stephen B. Dunnett * The aging septo-hippocampal system: Its role in age-related memory impairments / David S. Olton and Alicja L. Markowska * Neuromodulatory systems and the regulation of memory storage / James L. McGaugh * Modulation of memory processing: Enhancement of memory in rodents and humans / Paul E. Gold * Toward a comprehensive account of hippocampal function: Studies of olfactory learning permit an integration of data across multiple levels of neurobiological analysis / Tim Otto and Howard Eichenbaum * The hippocampus and prefrontal cortex in learning and memory: An animal model approach / Gordon Winocur * Role of diencephalic lesions and thiamine deficiency in Korsakoff's amnesia: Insights from animal models / Philip J. Langlais * Thiamine deficiency as an animal model of diencephalic amnesia / Robert G. Mair, John K. Robinson and Susan M. Koger * Emotional memories in the brain / Joseph LeDoux * Analysis of aversive memories using the fear-potentiated startle paradigm / Michael Davis * Memory: A behavioristic and neuroscientific approach / Garth J. Thomas and J. M. Ordy * Beyond neuronal excitability: Receptive field analysis reveals that association specifically modifies the representation of auditory information / Norman M. Weinberger * Knowledge structures in temporally adaptive conditioned responding / John W. Moore Section III. Studies in birds and invertebrates * Memory, the hippocampus, and natural selection: Studies of food-storing birds / David F. Sherry * Studying stages of memory formation with chicks / Mark R. Rosenzweig, Edward L. Bennett, Joe L. Martinez, Jr., Paul J. Colombo, Diane W. Lee and Peter A. Serrano * On chicks and rosetta stones / Steven P. R. Rose * Molecular interrelationships between short- and long-term memory / Timothy E. Kennedy, Robert D. Hawkins and Eric R. Kandel * Analysis of short- and long-term enhancement produced by one-trial conditioning in Hermissenda: Implications for mechanisms of short- and long-term memory / Terry J. Crow * Snails' tales: Initial comparisons of synaptic plasticity underlying learning in Hermissenda and Aplysia / Gregory A. Clark and Erin M. Schuman